Charmonium and e+e- pair photoproduction at mid-rapidity in ultra-peripheral Pb-Pb collisions at √sNN=2.76 TeV - Abbas, E.; Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agnello, M.; Agocs, A. G.; Agostinelli, A.; Ahammed, Z.; Ahmad, N.; et al. (SPRINGER, 2013)
The ALICE Collaboration at the LHC has measured the J/psi and psi' photoproduction at mid-rapidity in ultra-peripheral Pb-Pb collisions at root s(NN) = 2.76 TeV. The charmonium is identified via its leptonic decay for events where the hadronic activity is required to be minimal. The analysis is based on an event sample corresponding to an integrated luminosity of about 23 mu b(-1). The cross section for coherent and incoherent J/psi production in the rapidity interval -0.9 e(+)e(-) has been measured and found to be in agreement with models implementing QED at leading order.
Keywords: J/PSI PHOTOPRODUCTION; PHYSICS